A two-degree-of-freedom string-driven rotor for efficient energy harvesting from ultra-low frequency excitations. (1st April 2020) - Tan, Qinxue; Fan, Kangqi; Tao, Kai; Zhao, Liya; Cai, Meiling
Abstract: The aim of this study is to report a two-degree-of-freedom (2-DOF) string-driven rotor to convert ultra-low frequency vibrations to high-speed rotation motion of a rotor, which enables the efficient exploitation of ultra-low frequency mechanical energy. The proposed rotor structure consists of a disk-shaped rotor, a spring and two pieces of string, featuring extremely simple configuration. Based on the proposed rotor, we designed an electromagnetic energy harvester (EMEH) to show the feasibility of utilizing the rotor to achieve improved energy harvesting performance. Experimental results showed that the fabricated harvester with various structural parameters could provide two peak power outputs and generate up to 9.4 mW power when actuated at 3 Hz by a displacement excitation with an amplitude of 8 mm. With the electric power converted from the treadmill vibration by the EMEH, a hygrothermograph could be continuously driven to work with full functionality. Under the manual operation, the harvester could also sustainably charge some portable electronic gadgets. The results of this study exhibit the promising potential of the proposed rotor in efficiently harvesting the ambient ultra-low frequency energy. Highlights: A novel 2-DOF string-driven rotor is proposed. The 2-DOF rotor features a very simple structure. The 2-DOF rotor can convert ultra-low frequency vibrations to high-speed rotation. The harvester can provide high output power under ultra-low frequency excitations. The harvester can sustain the normal operation of various small electronic devices.